Students’ cognitive engagement through educard in learning vocabulary - Hernawati Hernawati; Yousef Bani Ahmad; Hilmansyah Saefullah (Journal of Education, Social & Communication Studies, 2024)
This study was investigating the students’ cognitive engagement in learning vocabulary through Educard media. The objectives of this study were to find out the way Educard facilitates the students’ cognitive engagement in learning vocabulary through Educard and students’ responses. The participants of this research are five students of eighth grade in one of junior high school. This study used a qualitative approach. The data were collected through interviews with five students of eighth grade and documentation. The research result showed that the students are facilitated by using Educard as learning media to learn vocabulary and engage them cognitively. The students experience many kinds of cognitive engagement while using Educard to learn English vocabulary including self-regulated learning, resource management, recipients, and task focus. Moreover, Educard builds them cognitive activities in learning vocabulary.